2018
DOI: 10.1016/j.hpb.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The extent of vascular resection is associated with perioperative outcome in patients undergoing pancreaticoduodenectomy

Abstract: The risk of significant morbidity and mortality for PDVR is associated with the extent of vascular resection, with graft repairs having increased morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…As expected, both the operative time and blood loss were significantly higher when a venous resection was associated with PD (17). More recent data on larger number of patients have confirmed that increased morbidity and mortality rates should be expected when a venous resection is associated with PD (37). In the present cohort, a portal vein/ superior mesenteric vein resection was performed in 14.3% of PDs.…”
Section: Discussionsupporting
confidence: 59%
“…As expected, both the operative time and blood loss were significantly higher when a venous resection was associated with PD (17). More recent data on larger number of patients have confirmed that increased morbidity and mortality rates should be expected when a venous resection is associated with PD (37). In the present cohort, a portal vein/ superior mesenteric vein resection was performed in 14.3% of PDs.…”
Section: Discussionsupporting
confidence: 59%
“…Few reports of rate of vascular resection in a complete population exist to date. Two recent analyses from the US NSQIP database used a similar definition and methodology to the current study, and reported equal, 22 or lower, 29 rates of vascular resections.…”
Section: Hpbmentioning
confidence: 87%
“…Chandrasegaram et al showed that the overall mortality associated with early SMV-PV thrombosis after pancreatectomy with or without grafts was 40% (8/20) compared to 11.1 % (3/27) in this systematic review after pancreatectomy with grafts [11,[13][14][15] . Kantor et al analyzed 640 patients undergoing pancreatoduodenectomy with venous resection in the American College of Surgeons National Surgical Quality Improvement Project from 2006 to 2013 [16] . Of these 224 patients had a graft repair that was associated with increased overall morbidity (58.7 %, p<0.01) and 30-day mortality rates (21 of 229, 7.7 %, p<0.01) [16] .…”
Section: Discussionmentioning
confidence: 99%